Foreign direct investment in GCC countries: The essential influence of governance and the adoption of IFRS - Costas Siriopoulos; Athanasios Tsagkanos; Argyro Svingou; Evangelos Daskalopoulos (Journal of Risk and Financial Management, 2021)
This paper presents an analysis of the factors affecting foreign direct investments, focusing on governance quality and adoption of International Financial Reporting Standards on countries of the Gulf Cooperation Council, which are a special case of study due to their idiosyncratic characteristics, rich natural resources and geographical position. Panel data analysis was conducted, implementing three different models (Fixed Effect, Random Effect, and Arellano Bond Dynamic Model). The results show that the adoption of International Financial Reporting Standards is a strong determinant that promotes foreign direct investments. As regards the governance quality, the block of Gulf Cooperation Council countries has fulfilled the minimum level of governance pre-conditions relative to foreign direct investments. In addition, governance indicators associated with law, rules, and corruption are more influential determinants for foreign direct investments.
Keywords: 330; FDI; GCC countries; governance; IFRS; OLI Paradigm; panel data analysis